1999
DOI: 10.1074/jbc.274.37.26065
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Topology of CzcA, a Cation/Proton Antiporter of the Resistance-Nodulation-Cell Division Protein Family

Abstract: The membrane-bound CzcA protein, a member of the resistance-nodulation-cell division (RND) permease superfamily, is part of the CzcCB 2 A complex that mediates heavy metal resistance in Ralstonia sp. CH34 by an active cation efflux mechanism driven by cation/proton antiport. CzcA was purified to homogeneity after expression in Escherichia coli, reconstituted into proteoliposomes, and the kinetics of heavy metal transport by CzcA was determined. CzcA is composed of 12 transmembrane ␣-helices and two large perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
170
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 47 publications
7
170
0
1
Order By: Relevance
“…Interestingly, even with the F 1 ATPase, alteration of the adenosine-binding pocket (28) by site-directed mutagenesis not only reduced the affinity of the substrate to the enzyme, but also created a clearly detectable positive cooperativity (29). We also note that positively cooperative kinetics was reported in an early reconstitution study of an RND pump, CzcA transporter, which catalyzes the export of toxic divalent metals (30), although the curves were drawn on only 4 points and the K 0.5 value reported was 6.6 mM, a concentration several orders of magnitude higher than that expected for the exclusion of toxic metals. The turnover number of the AcrB was rather small for nitrocefin, but it was about 2 orders of magnitude higher for cephalosporins like cephalothin and cephaloridine.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, even with the F 1 ATPase, alteration of the adenosine-binding pocket (28) by site-directed mutagenesis not only reduced the affinity of the substrate to the enzyme, but also created a clearly detectable positive cooperativity (29). We also note that positively cooperative kinetics was reported in an early reconstitution study of an RND pump, CzcA transporter, which catalyzes the export of toxic divalent metals (30), although the curves were drawn on only 4 points and the K 0.5 value reported was 6.6 mM, a concentration several orders of magnitude higher than that expected for the exclusion of toxic metals. The turnover number of the AcrB was rather small for nitrocefin, but it was about 2 orders of magnitude higher for cephalosporins like cephalothin and cephaloridine.…”
Section: Discussionmentioning
confidence: 95%
“…The E417K substitution yielded a normally expressed MexF protein (Fig. 2) (5). Since the drugtransporting pumps Acr and Mex are able to extrude uncharged hydrophobic molecules like organic solvents and chloramphenicol, it was proposed that a charge relay system was not involved in drug/proton translocation (5, 31).…”
Section: Resultsmentioning
confidence: 99%
“…Disp1 and Ptch1 share many characteristics with members of the resistance-nodulation-cell division (RND) family of protondriven transporters. Not only are the overall structures of Disp1 and Ptch1 similar to that of bacterial RND permeases, but aspartic acid residues in the fourth transmembrane span, which are thought to be important for proton translocation, are also conserved (Goldberg et al, 1999;Tseng et al, 1999). It has previously been shown that bacterial RND permeases function as trimers (Nagano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%